Design of Al-Islam Learning Media Based on Digital Storytelling on the Material of Emulating the Stories of the Ulul Azmi Apostles for Grade 5 Students of Mutu Elementary School, Nunukan - Azifatillah Azifah (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze and design Al-Islam learning media on the material of emulating the stories of the apostles Ulul Azmi through an engaging and effective digital storytelling approach to improve the understanding of fifth-grade students at SD MUTU Nunukan. Al-Islam learning, which emphasizes moral and spiritual values, requires innovative media to help students better understand and internalize exemplary attitudes from the prophets. The research method used is Research and Development (R&D) with the ADDIE model, which is limited to two stages: analysis and design. The analysis stage focuses on identifying student characteristics, learning needs, and curriculum requirements related to Al-Islam subjects. Meanwhile, the design stage involves planning digital storytelling-based learning media that integrates visual, audio, and narrative elements aligned with learning objectives. The designed media is expected to support student-centered learning, increase motivation, and make learning activities more meaningful. Through digital storytelling, students are encouraged to actively engage with the content, understand the moral values of the apostles Ulul Azmi, and apply these values in daily life.